Novel Fiber Bragg Grating Sensing Structure for Simultaneous Measurement of Inclination and Water Level - Cheng-Kai Yao; Yao-Jen Chung; Yong-Chang Xu; Pradeep Kumar; Peng-Chun Peng (Applied Sciences)
In the context of significant climate change, monitoring inclination, water levels, and temperatures in public buildings and surrounding environments is sensible. This paper presents a pair of fiber Bragg grating (FBG) subsidence sensor systems designed to simultaneously measure tilt and water levels and explore the system’s potential to detect temperature variations. The configuration of the FBG subsidence sensor is intentionally skewed to enhance measurement sensitivity. The system is capable of concurrently detecting a 0.5 cm variation in water level and a 0.424° change in tilt, with tilt measurements spanning from −1.696° to 1.696°. Furthermore, the measurement system can be integrated with free-space optics (FSO), which is anticipated to address the challenges associated with installing fiber optic cables. Consequently, the proposed innovative FBG sensor system can measure multiple parameters using fewer sensors, thereby improving sensing capacity and cost-efficiency.